Action of fat, four-jointed, dachsous and dachs in distal-to-proximal wing signaling. - Cho, E.; Irvine, K.D. (Development, 2004)
In the Drosophila wing, distal cells signal to proximal cells to induce the expression of Wingless, but the basis for this distal-to-proximal signaling is unknown. Here, we show that three genes that act together during the establishment of tissue polarity, fat, four-jointed and dachsous, also influence the expression of Wingless in the proximal wing. fat is required cell autonomously by proximal wing cells to repress Wingless expression, and misexpression of Wingless contributes to proximal wing overgrowth in fat mutant discs. Four-jointed and Dachsous can influence Wingless expression and Fat localization non-autonomously, consistent with the suggestion that they influence signaling to Fat-expressing cells. We also identify dachs as a gene that is genetically required downstream of fat, both for its effects on imaginal disc growth and for the expression of Wingless in the proximal wing. Our observations provide important support for the emerging view that Four-jointed, Dachsous and Fat function in an intercellular signaling pathway, identify a normal role for these proteins in signaling interactions that regulate growth and patterning of the proximal wing, and identify Dachs as a candidate downstream effector of a Fat signaling pathway.